Effective heat dissipation in an adiabatic near-field transducer for HAMR - Jennings, Brian; Bello, Frank; Donegan, John; Mc Closkey, David; Hobbs, Richard; Atcheson, Gwenael (My University, 2018)
To achieve a feasible heat-assisted magnetic recording (HAMR) system, a near-field transducer (NFT) is necessary to strongly focus the optical field to a lateral region measuring tens of nanometres in size. An NFT must deliver sufficient power to the recording medium as well as maintain its structural integrity. The self-heating problem in the NFT causes materials failure that leads tothe degradation of the hard disk drive performance. The literature reports NFT structures with physical sizes well below 1 micron which were found to be thermo-mechanically unstable at an elevated temperature. In this paper, we demonstrate an adiabatic NFT to address the central challenge of thermal engineering for a HAMR system. The NFT is formed by an isosceles triangular gold taper plasmonic waveguide with a length of 6 μm and a height of 50 nm. Our study shows that in the full optically and thermally optimized system, the NFT efficiently extracts the incident light from the waveguide core and can improve the shape of the heating source profile for data recording. The most important insight of the thermal performance is that the recording medium can be heated up to 866 K with an input power of 8.5 mW which is above the Curie temperature of the FePt film while maintaining the temperature in the NFT at 390 K without a heat spreader. A very good thermal efficiency of 5.91 is achieved also. The proposed structure is easily fabricated and can potentially reduce the NFT deformation at a high recording temperature making it suitable for practical HAMR application
PUBLISHED
Keywords: heat-assisted magnetic recording (HAMR) system; Plasmonics; Near-field optical recording; Thermal effects; Integrated optics devices; heat-assisted magnetic recording (HAMR) system